Healthcare Transformation - Tsang, Adrian (The Meducator, 2012)
In collaboration with the McMaster Health Forum Student Subcommittee, The Meducator is pleased to introduce ForumSpace, a column which aims to educate readers on current issues in the health sciences, particularly health policy, so as to engage students and promote active discussion. The Student Subcommittee oversees student-led activities designed to offer opportunities to explore issues of interest to McMaster students and the public, in line with a key mandate of the McMaster Health Forum—to nurture the leaders of tomorrow by exposing them to the leading thinkers and doers of today. This inaugural paper in the ForumSpace follows the event ‘Ill-Informed: The Future of Universal Healthcare in Canada’, held earlier this year, which inspired a small group of students to think further about these issues. Among them is the author of this article, Adrian Tsang, who is also a member of the Student Subcommittee. The aim of this article is to present some of those opinions and how they could contribute to the transformation of Canada’s healthcare system. The views expressed in this article are the views of the author and should not be taken to represent the views of the McMaster Health Forum.